Structure and phase behaviour of diblock copolymer monolayers investigated by means of Monte Carlo simulation. (28th September 2015) - Słyk, Edyta; Rżysko, Wojciech; Bryk, Paweł
Abstract: We use grand canonical Monte Carlo simulation paired with multiple histogram reweighting, hyperparallel tempering and finite size scaling to investigate the structure and phase behaviour of monolayers of diblock copolymers. The chain molecules are arranged on the square lattice and we consider both fully flexible and rod-coil polymer models. In contrast to the majority of previous studies we assume that the interactions between the segments belonging to one of the two subunits are weaker than the remaining segment–segment interactions. We find that when the diblock copolymer is fully flexible, this choice of the interactions leads to a suppression of the ordered phase, and the phase behaviour is analogous to that of the fully flexible homopolymer model. However, when one of the subunits is rigid, we observe the formation of a novel hairpin chessboard ordered structure with fully stretched chains bent in the middle. The topology of the phase diagram depends on the chain length. For shorter chains the global phase diagram features a critical point and a triple point. For longer chains the gas—disordered liquid phase transition is suppressed and only the order–disorder transition remains stable. The resulting phase diagram is of the swan neck type.